Tax Payer’s Tax Compliance Behavior, The Case Of Addis Ababa City Administration - Tsegaw, Geletaw (ABC Research Alert, 2017)
This paper attempted to reveal determinants of taxpayers’ tax compliance behavior. Six tax compliance determinants were examined; the examined tax compliance determinants were: tax knowledge; feeling of fairness; the influence of peer groups; income level of taxpayers; detection & punishments and perception on government spending. The study adopted a mixed method research approach to test the proposed hypotheses and to answer research questions. The data has been collected from 225 business profit taxpayers of those 200 were through distributing of self-administered questionnaires and the remaining 25 through in-depth interviews. The latest statistical package (SPSS) software, correlation and regression analysis, were used to analyze the survey and thematic analysis was applied to the in-depth interviews. The results of this combined research methodology suggest that Addis Ababa City business profit taxpayers tax compliance behavior have been highly and significantly affected by tax knowledge; feeling of fairness; the influence of peer groups; income level of taxpayers and detection & punishments variables while confidence in government spending doesn’t have as such significant impact on tax compliance behavior of businesses. The analysis focuses on tax compliance and its determinants and is therefore subject to an underlying assumption of tax payers' understanding of tax and other potentially relevant information. The results of this study also provide specific insights and allow policy makers to gain a better understanding of the key variables that are significantly associated with tax compliance and enable them to implement suitable strategies to minimize potentially damaging factors, and should also allow them to improve their government’s tax revenue collections. Such a study becomes imperative given limited research so far undertaken in the area. The present study may also be utilized to provide further information to assist tax authorities in designing full-fledged tax policies and in improving their respective tax collection mechanisms.